2020
DOI: 10.1021/acs.jpclett.0c00733
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Dependent Rate Constant Caused by Tunneling Effects: OH + HNO3 as an Example

Abstract: Tunneling effects on chemical reactions are well-known and have been unambiguously demonstrated by processes that involve the motion of hydrogen atoms at low temperature. However, the process by which tunneling effects cause a falloff curve (i.e., how reaction rate constants depend on pressure) has apparently not been previously documented. This work points out that falloff curves can indeed be caused by tunneling and explains the effect in simple terms. This is an interesting feature of quantum tunneling, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
3
6
0
Order By: Relevance
“…The proportional relationships between the tunneling effect factors at different pressures are the same as those of the rate constants, which explains the source of the pressure dependence for the H-abstraction rate constant. Our results are consistent with the previous study of Stanton and Stanton who concluded that it is the pressure dependence of the tunneling effect that leads to the pressure dependence of the H abstraction rate constants at low temperature.…”
Section: Resultssupporting
confidence: 93%
“…The proportional relationships between the tunneling effect factors at different pressures are the same as those of the rate constants, which explains the source of the pressure dependence for the H-abstraction rate constant. Our results are consistent with the previous study of Stanton and Stanton who concluded that it is the pressure dependence of the tunneling effect that leads to the pressure dependence of the H abstraction rate constants at low temperature.…”
Section: Resultssupporting
confidence: 93%
“…The resulting ATcT C-H 0 K bond dissociation energy of ethene producing vinyl, D 0 (H-CHCH 2 ) ¼ 456.41 AE 0.28 kJ mol À1 , and the equivalent 298. 15 , are, as expected, signicantly lower, since in this case the removal of the H atom is compensated by strengthening the C-C bond from an essentially single bond in ethyl to a canonical C]C double bond in ethene, as discussed previously. 91 Both bond dissociation energies, together with the current ATcT values for the other bond dissociations in the C 2 H n system, are for convenience summarized in Table 5.…”
Section: Atct Enthalpies Of Formationsupporting
confidence: 81%
“…Surprisingly, most available experimental results arise from indirect measurements, 4–10 and are thus highly uncertain. 2,5 In this work, we study the reversible reactions below (eqn (1) and (−2)) using parameters from a high accuracy thermochemistry method (ATcT) 11–13 and quantum chemical calculations, in combination with two-dimensional master equation techniques (2DME), 14–18 to obtain phenomenological rate constants as functions of both temperature and pressure.C 2 H 3 + H 2 ⇌ C 2 H 4 + HC 2 H 4 + H + M ⇌ C 2 H 5 + M…”
Section: Introductionmentioning
confidence: 99%
“…Related descriptions of pressure dependent bimolecular reaction rates arising from partial stabilization of a weak precursor complex have been presented by Canosa and coworkers 156 and by Nguyen and Stanton. 157…”
Section: Chemical Conversions and Rrkm Theorymentioning
confidence: 99%